Text Linguistics in Research Papers Prepared by University Students: Teaching through Lesson Plans and Textbooks - Albarrán-Santiago, Manuel (Revista Electrónica Educare, 2015)
This research project revolves around the properties of text linguistics under a qualitative approach.  The author analyzed drafts of a research paper by two university students as well as lesson plans and textbooks of high school Spanish Language and Literature courses and lesson plans of courses from the Licentiate degree in Education.  According to the information from the drafts, students struggle with coherence and cohesion in writing; however, they succeed in choosing the correct language for the type of writing.  Difficulties are most likely due to fact that this topic is not included in secondary education plans and is not commonly addressed in textbooks or university classes.  In conclusion, teachers should include the properties of text linguistics in their lesson plans in order to help students overcome these difficulties.